Analisis pembentukan ekspektasi wisata lewat fitur pendukung pencarian informasi di Instagram - Andini, Tania; Kurniawan, Firman (Jurnal Studi Komunikasi, 2020)
Social media basically reshapes the way information is distributed and consumed. Through user-generated content, Instagram users become active players and act as providers and connoisseurs of information. Instagram users can freely share their travel experiences through uploads that include hashtags and geotags. Through searching using hashtags and geotags, tourists can help with initial expectations. This study aimed to analyse the process of forming tourism expectations through hashtags and geotagging on social media Instagram. The research method used was a qualitative method with data collection through interviews with 10 informants. This study revealed the role of user involvement in hashtags and geotags in shaping expectations. Information search support features such as hashtags and geotags have been shown to support the formation of initial expectations of tourists, ranging from geographical descriptions of places to nearby accommodations. In addition, the visual content factor that attracts the attention and information contained in the content through the tag or text feature also plays a role for user decision making.